Environmental factors associated with disease progression after the first demyelinating event: results from the multi-center SET study - Horakova, Dana; Zivadinov, Robert; Weinstock-Guttman, Bianca; Havrdova, Eva; Qu, Jun; Tamaño-Blanco, Miriam; Badgett, Darlene; Tyblova, Michaela; Bergsland, Niels; Hussein, Sara; Willis, Laura; Krasensky, Jan; et al. (PloS one, 2013)
OBJECTIVES: To investigate the associations of environmental MS risk factors with clinical and MRI measures of progression in high-risk clinically isolated syndromes (CIS) after the first demyelinating event. METHODS: We analyzed 211 CIS patients (age: 28.9±7.8 years) enrolled in the SET study, a multi-center study of high-risk CIS patients. Pre-treatment samples were analyzed for IgG antibodies against cytomegalovirus (anti-CMV), Epstein Barr virus (EBV) early nuclear antigen-1 (EBNA-1), viral capsid antigen (VCA), early antigen-diffuse (EA-D), 25 hydroxy-vitamin D3 and cotinine levels and HLA DRB1*1501 status. The inclusion criteria required evaluation within 4 months of the initial demyelinating event, 2 or more brain MRI lesions and the presence of two or more oligoclonal bands in cerebrospinal fluid. All patients were treated with interferon-beta. Clinical and MRI assessments were obtained at baseline, 6, 12, and 24 months. RESULTS: The time to first relapse decreased and the number of relapses increased with anti-CMV IgG positivity. Smoking was associated with increased number and volume of contrast-enhancing lesions (CEL) during the 2-year period. The cumulative number of CEL and T2 lesions during the 2-year period was greater for individuals in the highest quartile of anti-EBV VCA IgG antibodies. The percent loss of brain volume was increased for those in the highest quartile of with anti-EBV VCA IgG antibodies. CONCLUSIONS: Relapses in CIS patients were associated with CMV positivity whereas anti-EBV VCA positivity was associated with progression on MRI measures, including accumulation of CEL and T2 lesions and development of brain atrophy.
Keywords: Adult; virus Epsteinův-Barrové - jaderné antigeny; HLA-DRB1 řetězec; Environment; Prospective Studies; Disease Progression; roztroušená skleróza; Antibodies, Viral; Humans; progrese nemoci; ženské pohlaví; Cohort Studies; mladý dospělý; dospělí; Smoking; kouření; Female; rizikové faktory; mužské pohlaví; Longitudinal Studies; Male; Young Adult; Epstein-Barr Virus Nuclear Antigens; prospektivní studie; životní prostředí; Cytomegalovirus; Risk Factors; Multiple Sclerosis; kohortové studie; lidé; longitudinální studie; protilátky virové; HLA-DRB1 Chains